School-Based Management and Learning Outcomes : Experimental Evidence from Colima, Mexico - Garcia-Moreno, Vicente; Gertler, Paul; Patrinos, Harry Anthony (World Bank, Washington, DC, 2019)
A school-based management program was implemented Mexico in 2001 and continued until 2014. This national program, Programa Escuelas de Calidad, was considered a key intervention to improve learning outcomes. In 2006, the national program was evaluated in the Mexican state of Colima, being the first experimental evaluation of the national program. All schools were invited to participate in the program; a random selection was performed to select the treatment and control groups among all the applicants. An intent-to-treat approach did not detect any impact on learning outcomes; a formal school-based management intervention plus a monetary grant was not enough to improve learning outcomes. First, the schools in the evaluation sample, control and treatment, were schools with high learning outcomes. Second, these schools had experienced some years of regular school-based management practices before the evaluation. A difference-in-difference design is used to identify heterogeneous effects of the program on learning outcomes. The difference-in-difference approach shows that the intensity of treatment increased test scores during the first year of the intervention.